Differential Expression of the Metabotropic P2Y Receptor Family in the Cortex Following Status Epilepticus and Neuroprotection via P2Y1 Antagonism in Mice - Alves, Mariana; Smith, Jonathon; Engel, Tobias (Frontiers in Pharmacology, 2020)
Purinergic signalling via P2 receptors is now widely accepted to play a critical role during increased states of hyperexcitability and seizure-induced pathology. In the setting of seizures and epilepsy, most attention has been paid to investigating the fast-acting ATP-gated P2X receptor family. More recent evidence has now also provided compelling evidence of an involvement of the slower-acting P2Y receptor family during seizures. This includes data demonstrating expression changes of P2Y receptors in the hippocampus following acute seizures and during epilepsy and anticonvulsive properties of P2Y-targeting drugs; in particular drugs targeting the P2Y1 subtype. Seizures, however, also involve damage to extra-hippocampal brain regions such as the cortex, which is thought to contribute to the epileptic phenotype. To analyse expressional changes of the P2Y receptor family in the cortex following status epilepticus and to determine the impact of drugs interfering with P2Y1 signalling on cortical damage, we used a unilateral mouse model of intraamygdala kainic acid-induced status epilepticus. Analysis of cortical tissue showed that status epilepticus leads to a global up-regulation of the P2Y receptor family in the cortex including P2Y1, P2Y2, P2Y4 and P2Y6, with the P2Y1 and P2Y4 receptor subtypes showing the strongest increase. Supporting a detrimental role of P2Y1 activation during status epilepticus, treatment with the P2Y1 agonist MRS2365 exacerbated high frequency high amplitude spiking, synonymous with injury-causing electrographic activity, and treatment with the P2Y1 antagonists MRS2500 protected against seizure-induced cortical damage. Suggesting P2Y1-mediated effects are predominantly due to increased microglia activation, treatment with the broad-spectrum anti-inflammatory drug minocycline abolished the observed neuroprotective effects of P2Y1 antagonism. In conclusion, our results further support a role for P2Y1-mediated signalling during seizure generation and seizure-induced neurodegeneration, suggesting P2Y1-targeting therapies as novel treatment for drug-refractory status epilepticus.